2018
DOI: 10.1111/mms.12472
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the abundance of Bristol Bay belugas with genetic mark‐recapture methods

Abstract: The Bristol Bay stock of beluga whales (Delphinapterus leucas) is genetically distinct and resides in Bristol Bay year-round. We estimated the abundance of this population using genetic mark-recapture, whereby genetic markers from skin biopsies, collected between 2002 and 2011, were used to identify individuals. We identified 516 individual belugas in two inner bays, 468 from Kvichak Bay and 48 from Nushagak Bay, and recaptured 75 belugas in separate years. Using a POPAN Jolly-Seber model, abundance was estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In conclusion, these data provide an initial population level audiogram for Bristol Bay belugas [26 of ca. 2000 animals (Allen and Angliss, 2012;Citta et al, 2018)] and are the first populationsubset audiograms for a healthy wild odontocete population. Animals overall showed sensitive hearing, with average hearing thresholds not exceeding mild hearing loss; this sensitivity is perhaps indicative of a relatively quiet habitat.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, these data provide an initial population level audiogram for Bristol Bay belugas [26 of ca. 2000 animals (Allen and Angliss, 2012;Citta et al, 2018)] and are the first populationsubset audiograms for a healthy wild odontocete population. Animals overall showed sensitive hearing, with average hearing thresholds not exceeding mild hearing loss; this sensitivity is perhaps indicative of a relatively quiet habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies revealed that the eight hypervariable microsatellite loci were highly informative in determining individual identity, assessing gene flow and population structure, and estimating first and second-order relationships in beluga whales 40 , 84 , 85 , 87 . These earlier studies also determined minimum allowable thresholds for missing data and genotyping errors and found that individual identity required a minimum of four of these loci 87 while accurate relatedness ( r ) estimation required a minimum of six loci genotyped per individual 40 . In the current study, we continued such tests by conducting analyses on datasets with individuals scored at ≥ six loci, ≥ seven loci, and all 8 nuclear loci.…”
Section: Methodsmentioning
confidence: 99%
“…This value approximates one individual (95% confidence interval: 0–8 individuals) over the last two generations, or roughly 58 years, based on a population of 300 individuals and a generation time of 29 years [ 86 ], although this estimate is rough due to uncertainty in all three estimates (migration rate, generation time, and population abundance), which compound in this calculation. Similarly, it is estimated from population genetic data that in the last ~ 60 years the Bristol Bay population may have received six immigrants from Cook Inlet (95% confidence interval 0–22 individuals) based on a population of 2000 individuals [ 35 ]. With connectivity this low between the two populations, their microbial communities are almost entirely isolated, which facilitates both random and adaptive divergence between them.…”
Section: Discussionmentioning
confidence: 99%
“…While the size of the beluga population in Bristol Bay is approximately 2000 individuals and has been steady or increasing [ 35 – 37 ], the population of beluga whales in Cook Inlet, Alaska, declined severely in the 1990s, attributed to unrestricted hunting by Alaska Natives [ 38 , 39 ]. It has not begun to recover despite a regional moratorium on hunting beginning in 2006 and was listed as Endangered under the U.S.…”
Section: Introductionmentioning
confidence: 99%